Enhanced efficacy of chemically modified curcumin in experimental periodontitis: systemic implications - Wang HH; Lee HM; Raja V; Hou W; Iacono VJ; Scaduto J; Johnson F; Golub LM; Gu Y (Dove Medical Press, 2019)
Howard H Wang, 1 Hsi-Ming Lee, 2 Veena Raja, 2 Wei Hou, 3 Vincent J Iacono, 4 Joseph Scaduto, 5 Francis Johnson, 6,7 Lorne M Golub, 2 Ying Gu 8 1Department of Periodontology and Endodontology, School of Dental Medicine, State University of New York at Buffalo, Buffalo, NY, USA; 2Department of Oral Biology and Pathology, School of Dental Medicine, Stony Brook University, Stony Brook, NY, USA; 3Department of Preventive Medicine, School of Medicine, Stony Brook University, Stony Brook, NY, USA; 4Department of Periodontology, School of Dental Medicine, Stony Brook University, Stony Brook, NY, USA; 5Traverse Biosciences Inc., Stony Brook, NY, USA; 6Department of Chemistry, Stony Brook University, Stony Brook, NY, USA; 7Department of Pharmacological Sciences, Stony Brook University, Stony Brook, NY, USA; 8Department of General Dentistry, School of Dental Medicine, Stony Brook University, Stony Brook, NY, USA Introduction: Dental microbial biofilm initiates gingival inflammation, and its suppression is the current dominant strategy for treating periodontitis. However, the host response to the biofilm is largely responsible for the connective tissue breakdown including alveolar bone loss, which is mediated by proinflammatory cytokines and matrix metalloproteinases (MMPs). Methods: The current study compared the efficacy of a novel host-modulation compound, a chemically modified curcumin (CMC 2.24), to that of its parent compound (natural curcumin), in both lipopolysaccharide (LPS) (a bacterial endotoxin)-induced cell culture and in vivo models of periodontitis. Results: In cell culture, both CMC 2.24 and curcumin appeared similarly effective in suppressing LPS-induced cytokine (IL-1β and TNF-α) secretion by mononuclear inflammatory cells; however, CMC 2.24 significantly reduced MMP-9 secretion by 78% (P< 0.05) whereas curcumin was ineffective. In vivo, CMC 2.24 administration was more effective than curcumin in suppressing (a) IL-1β in gingival tissue and (b) MMP-9 in both gingiva and plasma, the latter indicating a reduced severity of systemic inflammation. The difference in primary clinical outcome between the two treatments was that CMC 2.24 reduced the pathologically excessive alveolar bone loss, assessed morphometrically at multiple sites, by 80%– 90% (P< 0.01), whereas curcumin, surprisingly, either increased (P< 0.05) or had no effect on alveolar bone loss at these sites. Conclusion: These data, plus that from previous studies, support the therapeutic potential of CMC 2.24 in the management of inflammatory periodontal disease and its ability to reduce the risk of associated systemic diseases. The current study also indicates that the MMP-9 inhibitor efficacy is associated with the ability of CMC 2.24 (but not curcumin) to inhibit alveolar bone loss in this rat model of periodontitis. Keywords: chemically modified curcumin, cytokines, matrix metalloproteinases, MMPs, periodontitis, ratsCorrigendum for this paper has been published